Gas production and rumen fermentation characteristics of buffalo diets containing by-product from some sorghum varieties - Irawan Sugoro; Komang G. Wiryawan; Dewi Apri Astuti; Teguh Wahyono (Indonesian Center for Animal Research and Development (ICARD), 2015)
Sorghum is one of potencial fibre sources as buffalo feed. Quality of sorghum could be increased by irradiation mutation breeding. Samurai 1 and Samurai 2 were products of the irradiation mutation breeding of Pahat. This study was conducted to compare buffalo diets containing Samurai 2 sorghum straw and Samurai 1 bagasse sorghum compared with Pahat sorghum straw using in vitro study. Completely randomized design with 6 treatments and 3 replications was applied in this experiment. The treatment diets were P1 (50% Pahat sorghum straw + 50% concentrate), P2 (50% Pahat sorghum straw silage + 50% concentrate), P3 (50% Samurai 2 sorghum straw + 50% concentrate), P4 (50% Samurai 2 sorghum straw silage + 50% concentrate), P5 (50% Samurai 1 sorghum bagasse + 50% concentrate) and P6 (50% Samurai 1 sorghum bagasse silage + 50% concentrate). The 200 mg DM samples of diets were incubated in 30 ml rumen-buffer fluid for 48 hours. Variables measured were total gas production, CH4 production and rumen fermentation characteristics. Results showed that P2 and P4 produce the highest of gas production (P<0.05) with 60.99 and 60.86 ml/200 mg dry matter respectively. Treatments of P1, P2 and P4 produced the lowest CH4 concentration (P<0.05) with 10.57, 10.90 and 9.82% of total gas, respectively. The P4 produced the highest total volatile fatty acids (VFA), dry matter degradability and organic matter degradability with 109.83 mM, 62.93% and 59.97% respectively, meanwhile ammonia (NH3) concentration was not significantly different. The conclusion showed that straw silage of Samurai 2 was comparable to the Pahat sorghum straw and Samurai 1 bagasse sorghum as buffalo diet. Key Words: Buffalo, CH4 Concentration, Rumen Fermentation Characteristics, Sorghum